Strategi mitigasi risiko operasional pada perbankan syariah: Studi pada era digitalisasi - Iman, Dwiki Muhammad (Maliki Interdisciplinary Journal, 2026)
The development of digitalization has driven significant transformation in the Islamic banking industry, particularly in improving technology-based services. However, digitalization has also increased the complexity of operational risks, including information technology risks, cybersecurity, human error, Sharia compliance, and external risks. This study aims to analyze operational risk mitigation strategies in Islamic banking in the digital era. The method used is a descriptive qualitative approach through literature review from various scientific and regulatory sources. The results indicate that operational risk mitigation can be achieved through the implementation of Enterprise Risk Management (ERM), strengthening Good Corporate Governance (GCG), improving internal control systems, utilizing information security technology, and developing the quality of human resources. Furthermore, compliance with regulations stipulated by the Financial Services Authority (OJK) and the integration of Maqāṣid Sharia values ​​are important factors in maintaining stability and customer trust. Therefore, an effective and adaptive operational risk mitigation strategy is key to maintaining the sustainability of Islamic banking in the digital era.